Endophthalmitis caused by Kocuria kristinae: A Case Report - Alles, M.; Wariyapola, D.; Salvin, K.; Jayatilleke, K (Sri Lankan Journal of Infectious Diseases, 2020)
Kocuria kristinae is part of the microbiota of humans but can also act as an opportunistic pathogen causing invasive infection. Here we report a case of endophthalmitis in a previously healthy adult male, presumably resulting from iatrogenic infection due to intra-vitreal administration of drugs for the management of macular oedema. Following trans pars plana vitrectomy, an aseptically obtained specimen of vitreous humor was processed for bacterial culture. A pure growth of .kristinae was isolated, which was identified via VITEK 2. The patient was treated with intra-vitreal vancomycin with subsequent improvement of his condition.
10.4038/sljid.v10i2.8281
Keywords: Kocuria kristinae; Endophthalmitis; Vancomycin